Tracking Evidence and Informing Policy to Rebuild Livestock-Based Livelihoods and Empower Women in Conflict Affected Areas of Ethiopia - Terfa, Zelalem G. (CGIAR System Organization, 2024)
Over the past few years Ethiopia experienced conflicts and war resulting in displacement of millions of people and destroying social fabrics. Coupled with drought and locust, the conflicts destroyed livelihoods of farmers in war torn regions. Protracted conflicts also exacerbate gender inequalities and vulnerability of those population relying on agriculture for their livelihoods. Post-conflict, women continue to bear the brunt of the war due to destroyed livelihoods, trauma of rape, and the responsibility to feed the family. Therefore, livelihood rehabilitation efforts need to target women to make meaningful impact.